The tag SNP rs10746463 in decay-accelerating factor is associated with the susceptibility to gastric cancer. Issue 2 (February 2015) - Song, Qinqin; Zhang, Zhi; Liu, Yingwen; Han, Sugui; Zhang, Xuemei
Highlights We found DAF rs10746463 polymorphism effect on the risk of developing gastric cancer in Chinese population. We identified cigarette smoking modified the association of DAF variant with the risk of gastric cancer. Selected C3 tag-SNPs have no effect on the susceptibility to gastric cancer.